2015
DOI: 10.1002/lary.25333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of comorbid diabetes and hypercholesterolemia on the prognosis of idiopathic sudden sensorineural hearing loss

Abstract: Comorbid diabetes or hypercholesterolemia may indicate a smaller probability of major or moderate PTA improvement for patients with ISSNHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 41 publications
(88 reference statements)
2
48
2
5
Order By: Relevance
“…Presence of metabolic syndrome or CKD was also found to increase hearing level thresholds in a study conducted on Koreans. 6 Lin et al 10 found that comorbidity of diabetes hinders improvement from idiopathic sudden sensorineural hearing loss. Urine albumin excretion rate and serum creatinine levels were also associated with severity of hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of metabolic syndrome or CKD was also found to increase hearing level thresholds in a study conducted on Koreans. 6 Lin et al 10 found that comorbidity of diabetes hinders improvement from idiopathic sudden sensorineural hearing loss. Urine albumin excretion rate and serum creatinine levels were also associated with severity of hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking Gzms exhibited a reduced immune tolerance and increased inflammation levels through a type I interferon-dependent pathway, leading to the development of autoimmune diseases, including diabetes (43,45) and ulcerative colitis (46). These two autoimmune diseases were further associated with SNHL (47,48). Gzmm was proposed to be downregulated in AIED, which was in accordance with the results of the current study.…”
Section: Discussionmentioning
confidence: 97%
“…20 Another retrospective study analyzed hospital records of 781 patients with ISSNHL and concluded that steroid therapy yielded significant hearing improvement in patients with non-diabetes and hypercholesterolemia group. 21 …”
Section: Discussionmentioning
confidence: 99%